Pengembangan Pembelajaran Berbasis STEAM Bagi Guru Sekolah Dasar - Nadia Lutfi Choirunnisa; Suryanti Suryanti; Farida Istianah; Mintohari Mintohari; Julianto Julianto (Ilin Institute, 2023)
Changes in the independent curriculum have made many teachers unprepared with appropriate learning innovations to be applied. With the STEAM-Based Learning Development Training activity for elementary school teachers, it is expected to be a forum for teachers to be able to plan STEAM learning that can be applied in schools. The training was attended by 40 elementary school teachers in Magetan Regency, which was held offline and online. The implementation of this training uses The Training Cycle method, which includes analysis, planning, implementation, and evaluation of training. The results of the training that have been held show that participants gain new knowledge about STEAM learning and its implementation in the independent curriculum. In addition, the trainees get a new ability to create STEAM-based teaching modules.